2008
DOI: 10.1111/j.1601-6343.2008.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular joint adaptations following two‐phase therapy: an MRI study

Abstract: Forward relocation of the C-GF complex seems to be one of the mechanisms of action of functional appliances, while the internal anatomic arrangement within the temporomandibular joint (TMJ) complex normalizes to its pre-treatment position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
36
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 85 publications
9
36
0
3
Order By: Relevance
“…According to Wadhawan et al (15), the anterior repositioning of the condyle in the glenoid fossa caused by functional appliances results in stretching of the retrodiscal tissue that could lead to changes in the shape of the disk or its posterior displacement, which agrees with the study by Chavan et al (16). However, Aidar et al (1) found no significant changes in disk position after treatment with the Herbst appliance.…”
Section: Discussionsupporting
confidence: 79%
“…According to Wadhawan et al (15), the anterior repositioning of the condyle in the glenoid fossa caused by functional appliances results in stretching of the retrodiscal tissue that could lead to changes in the shape of the disk or its posterior displacement, which agrees with the study by Chavan et al (16). However, Aidar et al (1) found no significant changes in disk position after treatment with the Herbst appliance.…”
Section: Discussionsupporting
confidence: 79%
“…In orthodontic literature, temporomandibular joint (TMJ) adaptations following functional therapy have been visualized by various techniques like cephalograms, 1-3 panoramic radiographs, 4,5 computed tomography, 6,7 and magnetic resonance imaging. [8][9][10] However, there are many limitations to image acquisition of the TMJ using conventional techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, the literature provides limited data regarding the importance of the position of the MF and its interrelation with the craniofacial structures in the development of malocclusion. On the other hand, the application of orthopedic or orthodontics therapies has been described to produce some effects in the position or morphology of the MF [4,11,26,31,33,37,44,47,49,50,52].…”
Section: Introductionmentioning
confidence: 99%